Fruit and vegetable intake and the risk of gastric adenocarcinoma: a reanalysis of the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST) study after a longer follow-up - González, Carlos A.; Teucher, Birgit; Bläker, Hendrik (International journal of cancer, 2012)
In a previous European prospective investigation into cancer and nutrition (EPIC) analysis, we found an inverse association between total intake of vegetables, onion and garlic, and risk of intestinal gastric cancer (GC) and between citrus fruit and risk of cardia GC. The aim of this study is to reanalyze the effect of fruit and vegetables (F&V), based on a longer follow-up and twice the number of GC cases. Subjects are 477,312 men and women mostly aged 35 to 70 years participating in the EPIC cohort, including 683 gastric adenocarcinomas with 11 years of follow-up. Information on diet and lifestyle was collected at baseline. A calibration study in a subsample was used to correct for dietary measurement errors. When comparing the highest vs. lowest quintile of intake, we found an inverse association between total intake of V&F and GC risk [hazard ratio (HR) 0.77; 95% confidence interval (CI) 0.57-1.04; p for trend 0.02], between fresh fruit and risk of the diffuse type (HR 0.59; 95% CI 0.36-0.97; p for trend 0.03) and an inverse association between citrus fruit and risk of cardia cancer (HR 0.61; 95% CI 0.38-1.00, p for trend 0.01). Although calibration revealed somewhat stronger inverse associations, none of the risks reached statistical significance. There was no association between total or specific vegetables intake and GC risk. The inverse association between fresh fruit and citrus fruits and risk of GC seems to be restricted to smokers and the Northern European countries. Fresh fruit and citrus fruit consumption may protect against diffuse and cardia GC, respectively.
First published: 02 April 2012
Gesehen am 03.11.2018